Flexible conductive yarn and preparation method and application thereof

Through interfacial polymerization reaction and stretching and twisting steps, conductive yarns with excellent elasticity, strength and conductivity are prepared, which solves the problems of hard hand, insufficient strength and poor conductivity of conductive yarns in the prior art, and realizes the wide application of conductive yarns in various application fields.

CN119753908AActive Publication Date: 2025-04-04WUYI UNIV
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411827682.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-04-04
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

The prior art is difficult to prepare conductive yarns with good elasticity, high strength and good conductivity, the coating thickness is difficult to control, easy to fall off, and the yarn feels hard; the conductive nanomaterial blending method has uneven material distribution and insufficient strength, and the yarn is relatively brittle; electrospinning technology makes it difficult to ensure the strength of conductive fibers and is not easy to produce on a large scale.

Method used

Interfacial polymerization reaction is used to mix hexanediamine, conductive carbon material and oil-phase monomer solution to form a thin film, and conductive yarns are prepared by stretching, removing organic solvents and twisting.

Benefits of technology

The prepared conductive yarn has good elasticity, strength and conductivity, and is suitable for electromagnetic shielding materials, antistatic materials, smart textiles and wearable devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753908A_ABST
    Figure CN119753908A_ABST
Patent Text Reader

Abstract

The invention discloses a flexible conductive yarn and a preparation method and application thereof. The method comprises the following steps: S1, mixing a hexamethylenediamine solution, a conductive carbon material solution and an alkali solution to obtain a water-phase solution; mixing the water-phase solution and the oil-phase monomer solution and carrying out interfacial polymerization reaction to obtain a thin film; s2, stretching the film, removing the organic solvent, twisting, and drying to obtain the conductive yarn, the component of the oil-phase monomer solution comprises adipoyl chloride. The conductive yarn prepared by the method has the effects of good elasticity, high strength and good conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials, and in particular to a flexible conductive yarn and a preparation method and application thereof. Background Art

[0002] With the rapid development of science and technology, smart textiles and wearable technology have gradually become the focus of people's attention. In this field, conductive yarn, as its core basic material, plays a vital role. At present, the methods commonly used in the market to prepare conductive fibers or yarns include coating technology, conductive material blended chemical fiber spinning, and electrospinning technology. However, the thickness of the coating layer is not easy to control, it is easy to fall off, and the yarn feels hard; the conductive nanomaterial blended spinning method is prone to uneven material distribution, insufficient strength, and the yarn is relatively brittle; electrospinning technology is difficult to ensure the strength of the conductive fiber, and it is not easy to mass produce.

[0003] Therefore, it is of great significance to prepare a conductive yarn with good elasticity, high strength and good conductivity. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the first aspect of the present invention provides a method for preparing a flexible conductive yarn, wherein the conductive yarn prepared by the method has good elasticity, high strength and good conductivity.

[0005] The second aspect of the present invention also provides a flexible conductive yarn.

[0006] The third aspect of the present invention also provides an application of a flexible conductive yarn.

[0007] According to a first aspect of the present invention, a method for preparing a flexible conductive yarn is provided, comprising the following steps:

[0008] S1, mixing a hexamethylenediamine solution, a conductive carbon material solution and an alkaline solution to obtain an aqueous solution; mixing the aqueous solution and an oil phase monomer solution to perform an interfacial polymerization reaction to obtain a film;

[0009] S2, stretching the film, removing the organic solvent, twisting and drying to obtain the conductive yarn;

[0010] The components of the oil phase monomer solution include adipoyl chloride.

[0011] The preparation method according to the embodiment of the present invention has at least the following beneficial effects:

[0012] The present invention uses a mixture of hexamethylenediamine and graphene as an aqueous solution, and uses adipic acid amide as an oil solution. The oil solution is slowly poured into the aqueous solution to allow the two to undergo a polymerization reaction at the interface, and the obtained film is stretched and twisted to obtain a conductive yarn. The conductive yarn prepared by the method has the effects of good elasticity, high strength and good conductivity.

[0013] This is because the present invention firstly adopts specific hexamethylenediamine and adipoyl chloride as raw materials for polymerization reaction, and can have excellent elasticity and strength.

[0014] On the other hand, the conductive carbon material is in an aqueous solution and the interfacial polymerization technology is used to make the conductive carbon material stably and evenly distributed inside the yarn, thereby improving the conductivity of the conductive yarn.

[0015] According to some embodiments of the present invention, the mass concentration of the conductive carbon material solution is 3% to 10%. For example, the mass concentration of the conductive carbon material solution of the present invention is 3%, 5%, 8%, 10% or any sub-range of the two.

[0016] When the concentration of the conductive carbon material solution is less than 3%, the conductive properties of the conductive yarn will be affected; if the concentration of the conductive carbon material solution is higher than 10%, the strength of the conductive yarn will be affected. Therefore, the conductive yarn prepared within the above range has good conductivity and breaking strength.

[0017] According to some embodiments of the present invention, the conductive carbon material in the conductive carbon material solution is selected from at least one of graphene, carbon nanotubes, conductive carbon black or conductive carbon fiber.

[0018] According to some embodiments of the present invention, the mass concentration of the hexamethylenediamine solution in the aqueous phase solution is 3% to 5%.

[0019] According to some embodiments of the present invention, the mass concentration of adipoyl chloride in the oil phase monomer solution is 1.5% to 5%.

[0020] According to some embodiments of the present invention, the temperature of the interfacial polymerization reaction between the aqueous solution and the oily monomer solution is 10°C to 30°C.

[0021] According to some embodiments of the present invention, the interfacial polymerization reaction time is 1 to 20 seconds.

[0022] According to some embodiments of the present invention, the twist coefficient is 100-250.

[0023] According to some embodiments of the present invention, the twist coefficient is calculated by the following formula:

[0024] α=t*T^(1 / 2);

[0025] Where α is the twist coefficient; t is the twist, twist / 10cm; T is the yarn linear density, tex.

[0026] According to some embodiments of the present invention, the organic solvent in the oil phase monomer solution is selected from at least one of n-hexane, cyclohexane, n-heptane, n-octane or n-pentane.

[0027] According to some embodiments of the present invention, the alkali in the alkaline solution is selected from at least one of sodium hydroxide, potassium hydroxide, calcium hydroxide or barium hydroxide.

[0028] According to some embodiments of the present invention, in step S2, the method for removing the organic solvent is: mixing the stretched film with deionized water, heating the mixture, and then soaking and removing the mixture.

[0029] According to some embodiments of the present invention, the heating temperature is 40-60°C.

[0030] A flexible conductive yarn provided according to an embodiment of the second aspect of the present invention is prepared by the preparation method described in the first aspect of the present invention.

[0031] Thus, the prepared conductive yarn has good elasticity, high strength and good conductivity.

[0032] A third aspect of the present invention provides an application of the above-mentioned flexible conductive yarn in electromagnetic shielding materials, antistatic materials, smart textiles or wearable devices.

[0033] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0035] Figure 1 is a schematic diagram of a flow chart of Embodiment 1 of the present invention;

[0036] Figure 2 is a SEM image of the flexible conductive yarn prepared in Example 1 of the present invention;

[0037] Figure 3 This is the SEM image of the yarn prepared in Comparative Example 1. DETAILED DESCRIPTION

[0038] The following are specific embodiments of the present invention, and the technical solutions of the present invention are further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.

[0039] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0040] Some of the raw materials in the embodiments of the present invention are as follows:

[0041] Hexamethylenediamine: purchased from Macklin reagent;

[0042] Adipoyl chloride: purchased from Macklin reagent;

[0043] Conductive carbon material: graphene (CAS No. 7782-42-5); commercially available.

[0044] Example 1

[0045] This example provides a flexible conductive yarn. Figure 1 It is a flow chart, and its preparation method is as follows:

[0046] Hexamethylenediamine solution: prepare a hexamethylenediamine solution with a mass concentration of 4.0%;

[0047] Sodium hydroxide solution: prepare sodium hydroxide solution with a concentration of 3%;

[0048] Graphene solution: The mass concentration of graphene solution is prepared to be 10%;

[0049] Oil phase monomer solution: Adipoyl chloride and n-hexane were mixed to obtain an oil phase monomer solution with a mass concentration of 3.2%.

[0050] S1. Mixing a hexamethylenediamine solution, a sodium hydroxide solution and a graphene solution to obtain an aqueous solution; slowly pouring the oil phase monomer solution into the aqueous solution at 25° C. to perform an interfacial polymerization reaction for 10 seconds to obtain a black film;

[0051] S2. The black film is manually stretched, and the stretched filamentary film is immersed in 50° C. water for 30 minutes; the dried film filaments are taken out, twisted (twist coefficient is 114), and dried at 80° C. for 10 minutes to obtain the conductive yarn.

[0052] Example 2

[0053] This example provides a flexible conductive yarn, and its preparation method is basically the same as that of Example 1, except that the mass concentration of the graphene solution is 8%.

[0054] Example 3

[0055] This example provides a flexible conductive yarn, and its preparation method is basically the same as that of Example 1, except that the mass concentration of the graphene solution is 5%.

[0056] Example 4

[0057] This example provides a flexible conductive yarn, and its preparation method is basically the same as that of Example 1, except that the mass concentration of the graphene solution is 3%.

[0058] Example 5

[0059] This example provides a flexible conductive yarn, and its preparation method is basically the same as that of Example 1, except that the mass concentration of the graphene solution is 12%.

[0060] Example 6

[0061] This example provides a flexible conductive yarn, and its preparation method is basically the same as that of Example 1, except that the mass concentration of the hexamethylenediamine solution is 2.0%, the mass concentration of the sodium hydroxide is 1.4%, the soaking time is 30 minutes, and the twist coefficient is 154.

[0062] Example 7

[0063] This example provides a flexible conductive yarn, and its preparation method is basically the same as that of Example 1, except that the mass concentration of the oil phase monomer solution is 4.5%, the immersion time is 35 minutes, and the twist coefficient is 210.

[0064] Comparative Example 1

[0065] This example provides a flexible conductive yarn, and its preparation method is basically the same as that of Example 1, except that the aqueous solution does not contain a graphene solution.

[0066] Comparative Example 2

[0067] This example provides a flexible conductive yarn, and its preparation method is basically the same as that of Example 1, except that piperazine is used to replace hexamethylenediamine.

[0068] Comparative Example 3

[0069] This example provides a flexible conductive yarn, and its preparation method is basically the same as that of Example 1, except that isophthaloyl chloride is used to replace adipoyl chloride.

[0070] Performance Testing

[0071] The conductive yarn prepared in Example 1 of the present invention was subjected to SEM testing, and the results are as follows: Figure 2 As shown, Figure 2 a is the local morphology image, Figure 2 b is the overall morphology of the conductive yarn. Figure 2 It can be found that the surface of the conductive yarn with added graphene has high porosity.

[0072] The yarn prepared in Comparative Example 1 was subjected to SEM testing, and the results are as follows: Figure 3 As shown, Figure 3a is the local morphology image, Figure 3 b is the overall morphology of the conductive yarn. Figure 3 It can be found that, in comparison, the interfacial polymerization yarn without graphene has fewer pores on the surface, which indicates that the yarn without graphene has a compact structure, resulting in a decrease in porosity.

[0073] Furthermore, the conductive yarns prepared in the embodiments of the present invention and the comparative examples were subjected to the following tests; the results are shown in Table 1;

[0074] The resistance of the yarn is tested by a multimeter, the thickness of the yarn is tested by a handheld digital thickness gauge, the breaking strength and elongation of the yarn are tested by a tensile testing machine, the weight of the yarn is tested by an electronic balance, and the length of the yarn is measured by a vernier caliper.

[0075] The calculation formula of conductivity is:

[0076] σ=L / RS;

[0077] Where σ is conductivity, R represents resistance, Ω; S is cross-sectional area, m 2 ; L is length, m.

[0078] The calculation formula of linear density is:

[0079] Tt=1000G K / L;

[0080] Where Tt is the linear density, G k is the yarn weight, g; L is the yarn length, m.

[0081] Table 1

[0082] Conductivity (S / m) Breaking strength(MPa) Elongation at break Example 1 12.36 7.0 188% Example 2 8.72 7.3 192% Example 3 6.38 8.1 206% Example 4 4.04 10.5 212% Example 5 15.2 5.4 125% Example 6 12.26 7.6 214% Example 7 12.36 9.7 213% Comparative Example 1 0.01 11.8 223% Comparative Example 2 3.76 4.01 14.5% Comparative Example 3 5.54 3.29 8.9%

[0083] From the data in Table 1, it can be seen that the present invention uses interfacial polymerization technology to embed the conductive nanomaterial into the membrane material, and prepares a conductive yarn with good uniformity and high conductivity. In addition, through the analysis of the comparative examples and embodiments, it can be observed that the use of interfacial polymerization and twisting synergy technology not only effectively maintains the original elasticity of the yarn, but also ensures that the yarn has high strength and conductivity. This shows that the conductive yarn prepared by the scheme of the present invention has broad application prospects in the fields of electromagnetic shielding materials, antistatic materials and high-performance textiles.

[0084] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. A method for preparing a flexible conductive yarn, characterized in that: The steps include: S1, mixing a hexamethylenediamine solution, a conductive carbon material solution and an alkaline solution to obtain an aqueous solution; mixing the aqueous solution and an oil phase monomer solution to perform an interfacial polymerization reaction to obtain a film; S2, stretching the film, removing the organic solvent, twisting and drying to obtain the conductive yarn; The components of the oil phase monomer solution include adipoyl chloride.

2. The method for preparing the flexible conductive yarn according to claim 1, characterized in that: The mass concentration of the conductive carbon material solution is 3% to 10%.

3. The method for preparing the flexible conductive yarn according to claim 1 or 2, characterized in that: The conductive carbon material in the conductive carbon material solution is selected from at least one of graphene, carbon nanotubes, conductive carbon black or conductive carbon fibers.

4. The method for preparing the flexible conductive yarn according to claim 1 or 2, characterized in that: The mass concentration of the hexamethylenediamine solution in the aqueous phase solution is 3% to 5%.

5. The method for preparing the flexible conductive yarn according to claim 1 or 2, characterized in that: The mass concentration of adipoyl chloride in the oil phase monomer solution is 1.5% to 5%.

6. The method for preparing the flexible conductive yarn according to claim 1, characterized in that: The temperature of the interfacial polymerization reaction between the aqueous phase solution and the oil phase monomer solution is 10°C to 30°C.

7. The method for preparing the flexible conductive yarn according to claim 1, characterized in that: The twisting coefficient is 100-250.

8. The method for preparing the flexible conductive yarn according to claim 1, characterized in that: In step S2, the method for removing the organic solvent is: mixing the stretched film with deionized water, heating, and soaking to remove the organic solvent.

9. A flexible conductive yarn, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the flexible conductive yarn according to claim 9 in electromagnetic shielding materials, antistatic materials, smart textiles or wearable devices.

Citation Information

Patent Citations

  • Preparation method of interfacial polymerized film-like super absorbent resin

    CN110511316A

  • Amphiphilic graphene oxide modified ultrathin composite nanofiltration membrane, and preparation method and application thereof

    CN110559888A

  • Micro-channel reactor with support-body-free self-forming nylon membrane, and preparation method thereof

    CN110694563A

  • Preparation method and application of stretchable conductor with asymmetric structure

    CN116779241A

  • Antibacterial reverse osmosis composite membrane and preparation method thereof

    CN117138597A